Management of Al-Qur'an-Based Curriculum at Qur'an Hanifah Elementary School Semarang - Rahmawati, Anggun; Sutarto, Joko; Budi Utomo, Cahyo (Educational Management, 2021)
This study aims to analyze and describe how management of Qur'an-based curriculum consisting of planning, organizing, implementing and evaluating at SD Qur'an Hanifah Semarang. The research design used is a qualitative case study with data collection techniques through observation, interviews and documentation. The data used are primary and secondary data. Validity test of the data using source triangulation and data analysis using a flow model consisting of data collection, data reduction, data presentation, and verification or drawing conclusions. The research subjects are the principal, vice principal of the curriculum section, educators and education staff. The results of this study indicate that SD Qur'an Hanifah has implemented a Qur'an-based curriculum management process through four stages, namely planning, organizing, implementing and evaluating. Curriculum management planning at SD Qur'an Hanifah is carried out through an annual initial meeting involving various stakeholders through school-level and grade-level planning. The implementation and organization of the curriculum is carried out by the principal and the curriculum staff through the division of tasks, workloads and observations of the ongoing learning process based on the Qur'an-based curriculum. The evaluation which is the final stage is carried out by the principal using the CIPP (Context, Input, Process and Product) model. Overall, SD Qur'an Hanifah has carried out the stages of curriculum management well, although there are still some shortcomings and obstacles.